Element that affecting stock market performance in Malaysia / Muhammad Haziq Aiman A. Razak - A. Razak, Muhammad Haziq Aiman (2022)
The relationship between the immigration rate and the unemployment rate in Malaysia is investigated in this research. Malaysia is one country hat employed many foreign workers, and the country's economy is heavily reliant on them. Malaysia is one of the countries that largely relies on migrant labour, most of whom come from Indonesia, Bangladesh, and Nepal. Jobless people most likely top be affected by the immigrants. There are 28.7 million citizens and 3.3 million non-citizens in this population. One out of every ten people is a non-citizen. In 2010, 91.8 per cent of Malaysia's population (28.3 million people) were citizens, while 8.2 per cent were non-citizens. Generally, this research aims to investigate the factors that contributed to Malaysia's unemployment rate. There are few independences variable that used in this study such as immigration rate, wages and salaries, and gross domestic product. This study is using 30 years of observation from 1991 to 2020. The result findings from this study are there is no significant relationship between the immigration rate and the unemployment rate in Malaysia. Nest, there is also no significant relationship between the wages and salaries and the unemployment rate in Malaysia. Lastly, there is negative significant relationship between gross domestic product and the unemployment rate in Malaysia.